How can we better help cancer patients quit smoking? The London Regional Cancer Program experience with smoking cessation - Davidson, S.M. (Curr Oncol, 2018)
BACKGROUND: Because continued cigarette smoking after a cancer diagnosis is associated with detrimental outcomes, supporting cancer patients with smoking cessation is imperative. We evaluated the effect of the Smoking Cessation Program at the London Regional Cancer Program (lrcp) over a 2-year period. METHODS: The Smoking Cessation Program at the lrcp began in March 2014. New patients are screened for tobacco use. Tobacco users are counselled about the benefits of cessation and are offered referral to the program. If a patient accepts, a smoking cessation champion offers additional counselling. Follow-up is provided by interactive voice response (ivr) telephone system. Accrual data were collected monthly from January 2015 to December 2016 and were evaluated. RESULTS: During 2015–2016, 10,341 patients were screened for tobacco use, and 18% identified themselves as current or recent tobacco users. In 2015, 84% of tobacco users were offered referral, but only 13% accepted, and 3% enrolled in ivr follow-up. At the lrcp in 2016, 77% of tobacco users were offered referral to the program, but only 9% of smokers accepted, and only 2% enrolled in ivr follow-up. CONCLUSIONS: The Smoking Cessation Program at the lrcp has had modest success, because multiple factors influence a patient’s success with cessation. Limitations of the program include challenges in referral and counselling, limited access to nicotine replacement therapy (nrt), and minimal follow-up. To mitigate some of those challenges, a pilot project was launched in January 2017 in which patients receive free nrt and referral to the local health unit.